Automatic Detection of Swiss Cheese Polar Patterns on Mars Using Very High-Resolution Remote Sensing Images - Nascimento, Eduardo Soares [UNESP]; Cardim, Guilherme Pina [UNESP]; Pina, Pedro; Da Silva, Erivaldo Antonio [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2024)
With its polar caps and seasonal changes, Mars presents intriguing geological features such as the Residual South Polar Cap (RSPC) and its unique 'Swiss Cheese' depressions. These formations, caused by ice of CO2 sublimation, offer insights into Martian climatic dynamics. This study employs mathematical morphology and digital image processing techniques to automatically detect and analyze Swiss Cheese features on the RSPC. The methodology encompasses contrast enhancement, edge extraction, contour identification, and polygon filling. Statistical metrics evaluate the accuracy of the results. The methodology achieves high outcomes, with metrics surpassing 77%. Completeness, Correctness, Quality, and F1-Score consistently demonstrate the robustness of the methodology. The developed methodology successfully achieves its objectives, showcasing accurate detection and analysis of Swiss Cheese formations on Mars. This approach holds promise for broader planetary science investigations and highlights the potential of advanced image processing techniques.
Keywords: digital image processing; Mars; mathematical morphology; Residual South Polar Cap; Swiss Cheese features